ANALISIS EFISIENSI PEMASARAN BUAH STRAWBERRY DI DESA PANDANREJO KECAMATAN BUMIAJI KOTA BATU - ali rahman; Bambang Siswadi; Masyhuri Mahfudz (Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2019)
Abstract The research objective was to determine the corn marketing channel and the efficiency of corn marketing in Lenteng District, Sumenenp Regency. The data analysis method used is qualitative analysis and quantitative analysis which consists of three approaches namely (a) Marketing Margin (b) Market Integration and (c) Price Transmission Elasticity. The results of qualitative data analysis explain that there are two marketing channels, namely Channel I: Farmers, middlemen, Collector Traders, Channel II: Farmers, Middlemen, wholesalers, consumers. Channel III: farmers, middlemen, wholesalers, retailers, consumers. Marketing functions carried out by farmers: sales. Middlemen: purchases, weighing, loading and unloading, transportation and sales. Collectors: purchases, weighing, loading and unloading, transportation, packaging, depreciation, retribution and sales. Wholesalers: purchasing, weighing, loading and unloading, transportation, depreciation or sorting, levies and sales. The results of quantitative data analysis indicate that the market structure leads to the oligopoli market, this can be seen from the transmission price elasticity (η) of 1.7.Keyword : efficiency of marketing, strawberry fruit, line of marketing